Functional energetic landscape in the allosteric regulation of muscle pyruvate kinase. 3. Mechanism - Herman, Petr; Lee, J Ching (Biochemistry, 2009)
Mammalian pyruvate kinase exists in four isoforms with characteristics tuned to specific metabolic requirements of different tissues. All of the isoforms, except the muscle isoform, exhibit typical allosteric behavior. The case of the muscle isoform is a conundrum. It is inhibited by an allosteric inhibitor, Phe, yet it has traditionally not been considered as an allosteric enzyme. In this series of study, an energetic landscape of rabbit muscle pyruvate kinase (RMPK) was established. The phenomenon of inhibition by Phe is shown to be physiological. Furthermore, the thermodynamics for the temperature fluctuation and concomitant pH change as a consequence of muscle activity were elucidated. We have shown that (1) the differential number of protons released or absorbed with regard to the various linked reactions adds another level of control to shift the binding constants and equilibrium of active <--> inactive state changes (the latter controls quantitatively the activity of RMPK); (2) ADP plays a major role in the allosteric mechanism in RMPK under physiological temperatures (depending on the temperature, ADP can assume dual and opposite roles of being an inhibitor by binding preferentially to the inactive form and a substrate); and (3) simulation of the RMPK behavior under physiological conditions shows that the net results of the 21 thermodynamic parameters involved in the regulation are well-tuned to allow the maximal response of the enzyme to even minute changes in temperature and ligand concentration.
Keywords: aktivace enzymů; kosterní svaly; Animals; Rabbits; pyruvátkinasa; Enzyme Activation; počítačová simulace; Phenylalanine; vazba proteinů; energetický metabolismus; Energy Metabolism; Muscle, Skeletal; Adenosine Diphosphate; Computer Simulation; Ligands; chemické modely; adenosindifosfát; fenylalanin; alosterická regulace; Thermodynamics; Pyruvate Kinase; Models, Chemical; králíci; Allosteric Regulation; zvířata; termodynamika; Protein Binding; ligandy